A CONCEPTUAL FRAMEWORK FOR MANAGING RELATIONSHIPS BETWEEN ALL PARTICIPANTS DURING IT SERVICE AND SUPPORT ACTIVITIES - Leonard, A.C. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: Since the early days of computing, IT professionals have been struggling with their end users (customers) to such an extent that end users became sceptic about the quality of service and support IT professionals can offer. As such, relationships between IT professionals and end users were in many cases very poor, which impacts negatively on the efforts to use information technology to the advantage of organizations or communities as a whole. This paper briefly describes the historical reasons therefor and gives a theoretical foundation for the establishment of IT-end user relationships. The paper describes IT-end user relationships as intriguing and complex and proposes a conceptual framework that explains all the important elements involved during the establishment and maintenance of sound relationships as well as for managing change. This paper is based on a research study conducted into the working relationship between IT departments and its end users. The research was done by means of a qualitative approach in which thought experiments were used to inductively refine the results of the research study. AFRIKAANSE OPSOMMING:Sedert die ontstaan van die rekenaarwese en die gepaardgaande dienslewering via inligtingstegnologie bestaan die neiging by eindpuntgebruikers om skepties te staan teenoor die gehalte van diens wat deur inligtingstegnolo